Ag nanodot/Mg/Al reflective Ohmic contacts simultaneously suitable for n-type and p-type GaN. (25th May 2023) - Jin, Nan; Zhou, Yugang; Guo, Yan; Pan, Sai; Zhang, Rong; Zheng, Youdou
Abstract: This work reports on high-reflectivity Ag nanodot (AgND)/Mg/Al Ohmic contacts suitable for both p-GaN and n-GaN. The lowest specific contact resistances are found to be 2.25 × 10 −2 Ω·cm 2 on p-GaN and 2.56 × 10 −5 Ω·cm 2 on n-GaN. Ag was deposited and converted into AgNDs by annealing, and Mg/Al was then deposited. A second annealing process at different temperatures was performed to check the thermal stability of the contacts. Both the p-GaN and n-GaN contacts were Ohmic after annealing at 300 °C or below. The AgND/Mg/Al contacts annealed at 250 °C or less showed a reflectivity of over 91% for wavelengths from 400 to 550 nm. X-ray photoelectron spectroscopy and x-ray diffraction measurements were performed to investigate the contact mechanisms. We propose that in AgND/Mg/Al on p-GaN, the effective barrier is lowered due to the presence of an Ag2 O intermedia layer and the tunneling effect enables Ohmic contact. When the annealing temperature is 350 °C or higher, the Ag2 O changes to β -AgGaO2 or is decomposed and the height and width of the barrier for holes increase, which causes the Ohmic contact to deteriorate. The Ohmic behavior of AgND/Mg/Al contacts on n-GaN is assumed to be mainly due to the high direct coverage ratio of Mg and the good Ohmic contact behavior of Mg/n-GaN. These results show that AgND/Mg/Al Ohmic contacts can be fabricated simultaneously on both p-GaN and n-GaN, which is a possible solution for improving the density of both GaN-based ICs and micro-light emitting diodes (LEDs). This contact scheme can also improve the light output efficiency of GaN-based LEDs.